2017
DOI: 10.1155/2017/6085941
|View full text |Cite
|
Sign up to set email alerts
|

Surrounding Rock Deformation Mechanism and Control Technology for Gob-Side Entry Retaining with Fully Mechanized Gangue Backfilling Mining: A Case Study

Abstract: To counter the technical difficulties faced by gob-side entry retaining (GER) under multiple complex mining geological conditions in China, this paper introduces a GER method with fully mechanized gangue backfilling mining. A similar materials simulation experiment was conducted to simulate the gob-backfilled GER process by using the similar model test system containing an independently developed horizontal pushing load device. The experimental results show that the compaction speed of the backfilling area (BF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Zhang et al [19] studied the effect of different thicknesses of immediate roof on the deformation and fracture characteristics of roof in gob-side entry, and deduced a formula of rational support resistance of RSB. Gong et al [20] analyzed the effect of initial compaction of BFA on the deformation of retained entry roof and the stability of RSB by using physical simulation, which demonstrated the decisive effect of BFA granular gangue on the control of main roof deformation. Meanwhile, a RSB structure containing a flexible cushion was proposed, which can maintain a certain support force while adapting to the bending deformation of the roof, isolating crushed gangue from the gob, and limiting the deformation of the immediate roof.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [19] studied the effect of different thicknesses of immediate roof on the deformation and fracture characteristics of roof in gob-side entry, and deduced a formula of rational support resistance of RSB. Gong et al [20] analyzed the effect of initial compaction of BFA on the deformation of retained entry roof and the stability of RSB by using physical simulation, which demonstrated the decisive effect of BFA granular gangue on the control of main roof deformation. Meanwhile, a RSB structure containing a flexible cushion was proposed, which can maintain a certain support force while adapting to the bending deformation of the roof, isolating crushed gangue from the gob, and limiting the deformation of the immediate roof.…”
Section: Introductionmentioning
confidence: 99%
“…Gob-side entry retaining can enhance the coal recovery rate, reduce roadway drivage ratios and extend the service life of a mine. In general, an artificial wall is needed on the gob side of the entry so that the cross section of retained entry can still satisfy the service requirement after deformation [24]. During the early stage of C1661 mining, bagged gangue is used as the retaining wall along the side of a roadway, as shown in Figure 12.…”
Section: Gob-side Entry Retainingmentioning
confidence: 99%
“…In recent years, a great deal of research into RGE for FMLP has been carried out [5][6][7][8][9][10]. Many studies have indicated that the deformation and stress distribution of roadside backfilling body (RBB) play an important role in RGE [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%